Pengaruh Brand Image dan Brand Trust Terhadap Keputusan Pembelian Pada Produk Aqua - Sanjaya, Mochamad Ismail; Nurlenawati, Netti; Triadinda, Dexi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study was conducted to examine the extent to which brand image and brand trust on purchasing decisions influence consumer choices in purchasing Aqua products. The approach used is quantitative, where information is collected through questionnaires distributed to 97 respondents by applying the Lemeshow formula. Data processing is carried out using the SPSS application through a linear regression test. Research from this analysis indicates that brand image and brand trust individually do not have a significant influence on purchasing decisions, but when combined, both show a significant impact. The implications of this research state that in order to further understand buyer behavior patterns, it is necessary to explore other elements that have a stronger influence in driving purchasing decisions through further research.